Effect of plyometric training on swimming block start performance in adolescents - Bishop, D. C.; Smith, R. J.; Smith, M. F.; Rigby, H. E. (The Journal of Strength and Conditioning Research, 2009)
This study aimed to identify the effect of plyometric training (PT), when added to habitual training (HT) regimes, on swim start performance. After the completion of a baseline competitive swim start, 22 adolescent swimmers were randomly assigned to either a PT (n = 11, age: 13.1 ± 1.4 yr, mass: 50.6 ± 12.3 kg, stature: 162.9 ± 11.9 cm) or an HT group (n = 11, age: 12.6 ± 1.9 yr, mass: 43.3 ± 11.6 kg, stature: 157.6 ± 11.9 cm). Over an 8-week preseason period, the HT group continued with their normal training program, whereas the PT group added 2 additional 1-hour plyometric-specific sessions, incorporating prescribed exercises relating to the swimming block start (SBS). After completion of the training intervention, post-training swim start performance was reassessed. For both baseline and post-trials, swim performance was recorded using videography (50Hz Canon MVX460) in the sagital plane of motion. Through the use of Silicon Coach Pro analysis package, data revealed significantly greater change between baseline and post-trials for PT when compared with the HT group for swim performance time to 5.5 m (-0.59 s vs. -0.21 s; p < 0.01) and velocity of take-off to contact (0.19 ms-1 vs. -0.07 ms-1; p < 0.01). Considering the practical importance of a successful swim start to overall performance outcome, the current study has found that inclusion of suitable and safely implemented PT to adolescent performers, in addition to HT routines, can have a positive impact on swim start performance.